Methods for recording the time profile of single ultrashort pulses of electron beams and discharge currents in real‐time mode. Issue 1 (1st April 2016) - Tarasenko, Victor F.; Rybka, Dmitry V.
Abstract : The collectors for measuring the time profile of a current pulse of the runaway electron beam that are generated under atmospheric pressure are described. An analysis of changes in pulse shape depending on the bandwidth of the registration path with a temporal resolution of up to 20 ps was performed. It is shown that the electron beam detected behind small‐diameter diaphragms has a complex structure, which depends on the parameters of the gas diode. There is a design of the current shunts with a temporal resolution of up to 100 ps in this study. Measurement techniques of voltage pulses with subnanosecond and nanosecond duration are briefly described.